Manajemen Pembelajaran Tahfidz Qur’an dengan Metode Talaqqi di SDIT Ar Rahmah Pacitan - Suyitno, Suyitno; Markhamah, Markhamah; Sutama, Sutama (Lembaga Yasin AlSys, 2022)
Ar Rahmah Pacitan Integrated Islamic Elementary School is a school that implements the national curriculum and the unique curriculum of the Integrated Islamic School. One of its distinctive features is learning in Tahfidz Al-Qur'an,. This study aims to determine the management of Tahfidz Al-Qur'an learning based on the Talaqqi method in Ar Rahmah Pacitan Integrated Islamic Elementary School which includes planning, organizing, leadership, and learning evaluation. This study uses a qualitative approach and descriptive research methods. Data collection techniques include observation techniques, interviews and documentation studies. The results showed that Ar Rahmah Pacitan Islamic Elementary School had implemented learning management which included (1) planning for Tahfidz Al-Qur'an learning based on the talaqqi method including: first, determining student memorization targets; second, determine learning strategies and methods; third, determine the program of learning activities; fourth, determine the schedule and time for learning. (2) The organization of Tahfidz Al-Qur'an learning based on the talaqqi method is carried out to determine the structure and duties of the ustadz/ustadzah as well as the mechanism for learning Tahfidz Al-Qur'an. (3) Tahfidz Al-Qur'an learning leadership based on the talaqqi method is carried out by ustadz/ustadzah so that the implementation of learning runs in a conducive manner, which includes classroom management and learning activities. (4) Evaluation of Tahfidz Al-Qur'an learning based on the talaqqi method by looking at student learning outcomes and student abilities according to indicators that have been determined by the school